A crypto tax assessment index (C-TAI) for oil and gas industry - Mas'ud, Abdulsalam; Abd Manaf, Nor Aziah; Saad, Natrah; Abdo, Hafez (Elsevier, 2020)
In addition to conventional taxes, host oil and gas producing countries impose a “crypto tax”, including sustainability-related taxes similar to environmental taxes and social sphere development costs. These taxes aim to maximize government taxes which are collected to ensure operational efficiency and sustainable development. In contrast, multinational oil companies look beyond conventional taxes by performing a thorough assessment of “crypto tax” while deciding investment locations. Extractive industry taxation literature is limited in offering a scrupulous index. In particular, how a robust index is constructed and tested for these quasi-taxes. Therefore, the issues surrounding the construction and testing of Crypto Tax Assessment Index (C-TAI) underpins the relevance and motivations of this study. Specifically, this study aims to examine the construction and testing of a C-TAI in guiding policymakers and investors concerning crypto taxes. A properly constructed Index would enable governments to undertake environmental and sustainability assessment, knowing that the index suited their particular petroleum fiscal policy. The Malaysian marginal oil field sector was established to test internal and external validities and model fit indices of the C-TAI through surveying the opinions of experts in this field. Taking these views and opinions into consideration, in constructing an appropriate C-TAI, researchers can use the index address possible questions relating to the effects of crypto taxes on individual oil and gas projects or the overall petroleum sector of a country. For instance, how useful the constructed C-TAI could be in the examination the effect of crypto taxes on the profitability of a mature basin? How does the constructed C-TAI could be used in relation to the effect of crypto taxes on the profitability of marginal oil fields and the investment climate of a frontier petroleum basin? In answering these questions, it is anticipated that a properly constructed and robust C-TAI would help to guide policymakers and investors in understanding the importance of a C-TAI for crypto taxes, including sustainable developments.